Population Pharmacokinetics and Initial Dosage Optimization of Tacrolimus in Pediatric Hematopoietic Stem Cell Transplant Patients - Liu, Xiao-Lin; Guan, Yan-Ping; Wang, Ying; Huang, Ke; Jiang, Fu-Lin; Wang, Jian; Yu, Qi-Hong; Qiu, Kai-Feng; Huang, Min; Wu, Jun-Yan; Zhou, Dun-Hua; Zhong, Guo-Ping; et al. (Frontiers in Pharmacology, 2022)
Background: There is a substantial lack of tacrolimus pharmacokinetic data in paediatric hematopoietic stem cell transplant (HSCT) patients. This study aimed to evaluate the population pharmacokinetics (PopPK) of tacrolimus in paediatric HSCT patients and to devise model-guided dosage regimens. Methods: The retrospective study was conducted in 86 paediatric HSCT patients who received tacrolimus intravenously or orally. A total of 578 tacrolimus observations were available for pharmacokinetic analysis using non-linear mixed-effects modeling method. Demographic and clinical data were included and assessed as covariates via the stepwise method. Bayesian estimators were used to devise paediatric dosage regimens that targeted trough concentrations (C0) of 5-15 ng·mL-1. Results: A one-compartment model with first-order absorption was adequately described the tacrolimus pharmacokinetics. The clearance (CL), the volume of distribution (V), and typical bioavailability (F) in this study were estimated to be 2.42 L/h (10.84%), 79.6 L (16.51%), and 19% (13.01%), respectively. Body weight, hematocrit levels, post-transplantation day, and the co-therapy drugs (azole antifungal agents and caspofungin) were considered as significant covariates on the CL. Hematocrit levels were found to have a significant impact on the V of tacrolimus. In the subgroup cohort of patients (n=24) who had CYP3A5 polymorphism information, patients carried CYP3A5*3 had 1.38-fold higher CL than the non-carriers. Simulation revealed that the optimized initialing dose of tacrolimus for intravenous and oral administration could be 0.025 and 0.1 mg·kg-1·d-1 (q12 h), respectively. Conclusions The developed PopPK model described well the concentration-time profiles for tacrolimus in paediatric HSCT patients. Model-devised dosage regimens provide a practical strategy for achieving the tacrolimus therapeutic range and therefore improving clinical effectiveness.